Analisis Dasar Penilaian Kinerja PT. Astra Agro Lestari Tbk, dengan Menggunakan Alat Ukur Pusat Investasi ROI (Return On Investment) - Herlina Rumiyati; Anggita Zulvianti; Irna Nurhusyaini Ridwan; Muhamad Dika Risky Nur Fausta (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study employs Return On Investment (ROI) as a key metric to evaluate the financial performance of PT Astra Agro Lestari Tbk. The selection of ROI is justified by its capacity to comprehensively assess the efficiency of the company's total operational assets in profit generation. Utilizing a descriptive research design, the analysis is based on secondary data extracted from the company's financial statements available through the Indonesia Stock Exchange. The research reveals that PT Astra Agro Lestari Tbk achieved an ROI of 78%, indicating superior efficiency in investment management. These empirical findings provide valuable insights for corporate management to formulate strategic decisions aimed at enhancing future operational performance.